Monetary Policy and Return on Equity of Quoted Insurance Firms: A Time Series Study from Nigeria - Minafuro Suzane, Macfubara; Dumbor, Norteh; Barida Barry, Gberesuu (American Finance & Banking Review, 2018)
The financial system is the transmission channel of monetary policy. This study examines the effect of monetary policy on the performance of insurance firms in Nigeria from 1990 – 2017. The objective is to investigate the existing relationship between monetary policy instruments and the performance indicators of insurance companies. Secondary data were sourced from Stock Exchange factbook, Central Bank of Nigeria (CBN) Statistical Bulletin. Multiple linear regressions were formulated to examine the effect of the independent variables on the dependent variable. Return on equity was modeled as a function of treasury bill rate, monetary policy rate, interest rate, growth of money supply and exchange rate. R2, T-Statistics, β Coefficient, F-Statistics and Durbin Watson were used to examine the extent to which the independent variables affect the dependent variables while augmented dickey fuller unit root test, granger causality test, cointgration test and error correction models was used to ascertain the dynamic relationship between monetary policy variables and return on equity of the insurance firms. Findings revealed that, all the explanatory variables have positive effect on return on equity except treasury bill rate. The unit root test found that the variables are stationary at first difference, the cointgration test found the presence of long run relationship while the granger causality test found a uni-directional causality. The study concludes that monetary policy has moderate effect on the return on equity of the insurance firms. We recommend that management of insurance companies should devise measures of managing the negative effects of the monetary policy instruments to enhance the performance of the insurance companies.